Structure of the Bay of Bengal oxygen deficient zone. (September 2020) - D'Asaro, Eric; Altabet, Mark; Kumar, N. Suresh; Ravichandran, M.
Abstract: Oxygen levels within the oxygen deficient zone (ODZ) of the Bay of Bengal are mapped using 11 ARGO floats spanning 5 years. North of about 18°N in the ODZ 'core', minimum oxygen levels are uniformly below ~1 μmol kg −1 . South of this, in the ODZ 'edge', oxygen levels increase toward an average of about 7 μmol kg −1 at 10°N, but with high variability so that values below ~1 μmol kg −1 occur at all latitudes. This variability is consistent with simple models of mesoscale eddy stirring which suggest an exchange time for the core of about 1 year. Existing measurements of microbial transformation of nitrate to N2 in the Bay of Bengal have only been made in the edge region and may underestimate rates in the core region with lowest O2 concentration and thus the overall N transformation rates in this ODZ.